The uses and abuses of power: teaching school leadership through children's literature - Thomson, Pat (Taylor & Francis, 2014)
There are relatively few studies of how representations of teachers, schools and educational administrators in popular films and television might be, and are, used in leadership preparation. This paper seeks to add to this small body of work; it reports on an exploratory study of the representation of headteachers in contemporary children's fiction. Thirty-one texts are analysed to ascertain key themes and the major characterisations. The paper draws on children's literature scholars to argue that both the historical school story and its contemporary counterpart focus heavily on the power of the head to control the micro-world of the school. Because these fictional accounts deal with issues of power and justice more openly than many mainstream educational administration texts, this makes them particularly useful in the preparation of potential school leaders.